Enhancement drugs and the athlete - Botre, F.; Pavan, A. (Physical Medicine & Rehabilitation Clinics of North America, 2009)
This article considers the health risks associated with the abuse of performance-enhancing drugs (PEDs) in sport. After an overview on the evolution of doping substances and methods and on the current international organization of the antidoping tests, the potential risks correlated with abuse of PEDs are presented. Specific problems of drug associations, designer steroids, and nutritional supplements also are discussed. Data from randomized clinical trials may not be sufficient to identify the complete range of adverse effects possible with abuse of PEDs; more specific studies are necessary to assess their actual toxic potential.